Momentum analyticity of the holographic electric polarizability in 2 + 1 dimensions - Lei Yin; Hai-cang Ren; Ting-Kuo Lee; Defu Hou (Journal of High Energy Physics, 2017)
Abstract The static electric polarization of a holographic field theory dual to the Einstein-Maxwell theory in the background of AdS 4 with a Reissner-Nordström (AdS-RN) black hole is investigated. We prove that the holographic polarization is a meromorphic functions in complex momentum plane and locate analytically the asymptotic distribution of the poles along two straight lines parallel to the imaginary axis for a large momentum magnitude. The results are compared with the numerical result on Friedel-like poles of the same holographic model reported in the literature and with the momentum singularities of the one-loop polarization in weak-coupling spinor QED3 and scalar QED3 with the similarities and differences discussed.